2013
DOI: 10.1111/jzo.12013
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns and masses of the heads and necks of male and female giraffes

Abstract: We have analyzed the growth patterns of the head and neck of 65 male and 71 female giraffes from two different populations of giraffes, and also the dimensions of 19 different components of the head and neck in 8 female and 13 male giraffes, to establish if they showed sexual dimorphism and if sexual selection for a weapon was a possible origin of the long neck of giraffes. We found that in both genders the rate of increase in head mass was hypoallometric with respect to body mass. The rate of increase in neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 43 publications
0
19
2
Order By: Relevance
“…Masseter muscle mass has been reported in a single captive giraffe by Clauss et al (2008) and by us in wild giraffes in the context of the anatomy of their head and skull and not digestion (Mitchell et al, 2013B). Similarly, we have reported mandible mass, and tongue length and mass (Mitchell et al, 2013B).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Masseter muscle mass has been reported in a single captive giraffe by Clauss et al (2008) and by us in wild giraffes in the context of the anatomy of their head and skull and not digestion (Mitchell et al, 2013B). Similarly, we have reported mandible mass, and tongue length and mass (Mitchell et al, 2013B).…”
Section: Introductionmentioning
confidence: 58%
“…They also have a unique tapetum lucidum which enhances vision in mesopic light (Coimbra et al, 2013). Moreover, with age their visual field becomes more binocular and near distance stereoscopic visual acuity increases (Mitchell et al 2013B). Stereoscopic vision, together with their ability to discriminate between closely spaced objects that the large number of photoreceptors confers, enhances their ability to discriminate between sizes and shapes of browse and thus selectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been popularly demonstrated that this adaptation permits giraffes to use vegetation at higher levels from the ground, therefore outcompeting the shorter-necked herbivores, and allows for a specialized mode of fighting for male dominance in mating, termed ‘necking’ [1,2]. Analysis of rate of neck mass increase found little difference between male and female giraffes, suggesting a smaller role of sexual selection in the elongation of the neck [3]. It has been proposed that both foraging and male combat probably contributed to giraffe neck lengthening; observation of giraffes browsing from tree heights up to 5 m favours the ‘competing browsers’ hypothesis, and the direct selection of larger-necked males by oestrous females supports the sexual selection theory [4].…”
Section: Introductionmentioning
confidence: 99%
“…We did not expect to find sexual dimorphism between equivalent body mass giraffes, and we did not find any. Our expectation was based on the lack of dimorphism in giraffe neck length and cervical vertebrae growth patterns (Mitchell et al, ; van Sittert et al, ). The results we report here further confirm that sexual selection has not played a major (if any) role in the evolution of tallness in giraffes.…”
Section: Discussionmentioning
confidence: 99%